New Balance of Power in the Global Foreign Exchange Market - BERTAYEVA, Kulyash Jazikbayevna; ONALTAYEV, Darkhan Onaltayevich; ZHAGYPAROVA, Aida Oryntaevna (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The present paper gives an analysis of the current situation in the global foreign exchange and financial markets, which are directly related to the volatility of the reserve currency – the US dollar. The purpose of this article is to make changes in a coherent theoretical concept of formation and development of the global foreign exchange market, to develop the main directions for the reorganization of the global monetary system and to elaborate the suggestions about the present place and role of the reserve currency. Currently, many countries, such as Russia, China, Brazil and others, are pursuing their monetary policy, which consists in abandoning the US dollar in international trade transactions and creating their own monetary union. On the one hand, this research emphasizes the possibility of the collapse of the US currency and the development of a new reserve currency, and on the other hand – proves the strengthening of the US dollar, since the US has never been concerned about external obligations due to the status of its currency as a reserve currency. Therefore, there is a dilemma that is difficult to solve without the recommendations of the IMF and other international organizations.